Unpaid Work as a Potential Support for Employment in the Labour Market - Martinkovicova, Miriam; Povazanova, Mariana; Kasca´kova, Alena (Olsztyn Economic Journal, 2014)
This paper considers the problem of unpaid work in households. It focuses on the different categories of unpaid work, particularly the implementation of housework, child care and adult care. Specifically, household services, and domestic care services with included health services are designated as "white jobs" which may have the potential to create new jobs. These "white jobs" represent an untapped source of employment in the labour market. The main objective of the paper is to explore the various social determinants influencing the decision of Slovak families to use or not use alternative market substitutes of selected categories of unpaid work with the aim of identifying the hidden potential for job opportunities in the labour market in Slovakia and the potential demand for those services. The results of the primary research suggests that Slovak households have a potentially greater interest in procuring household services from external sources, rather than procuring personal services for themselves. In terms of the perspective demand for the above mentioned services, the research found that in this case it should be necessary to take into consideration the strong influence of traditionalism and conservatism, which affects the scope and nature of market substitute usage.